PENGARUH OPINI AUDIT, REPORTING DELAY, PROFITABILITAS, SOLVABILITAS, DAN LIKUIDITAS TERHADAP HARGA SAHAM - Rizky Herlambang (JAMER : Jurnal Akuntansi Merdeka, 2024)
This study aims to examine the effect of Audit Opinion, Reporting Delay, Profitability, Solvency, and Liquidity on Stock Prices. The technique of taking samples using purposive sampling method. The data used in this study is secondary data in the form of annual financial reports from 32 banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 – 2021. Data analysis was carried out using the SPSS application version 25 for windows. The results of the T-TEST showed that the significance value of the audit opinion variable was 0.468, the significance value of the reporting delay variable was 0.840, the significance value of the profitability variable was 0.000, the significance value of the solvency variable was 0.543, the significance value of the liquidity variable was 0.011. Then the results of the F TEST obtain a probability value of 0.001 which is smaller than the significance value of 0.05. Based on these results it can be concluded that, partially, the profitability variable has a significant positive effect on stock prices and the liquidity variable has a significant negative effect on stock prices. while for the variable audit opinion, reporting delay, and solvency, have no significant effect on stock prices. Then simultaneously concluded that the variables of audit opinion, reporting delay, profitability, solvency, and liquidity together have a significant effect on stock prices.